Analysis of Fatty Acids in Breastmilk During a 9-month Lactation Period Using Gas Chromatography–Mass Spectroscopy (GC-MS) - Titin Aryani; Dwi Ernawati; Henny Parida Hutapea (Universitas 'Aisyiyah Yogyakarta, 2020)
Breastmilk is very much needed to meet the needs of babies in every way because it contains important nutrients, carbohydrates in the form of lactose, and fatty acids in the form of polyunsaturated fatty acids. Research on fatty acid content in breastmilk with a lactation period of 9 months is needed to provide information to the public related to fatty acid content of breastmilk during 9 months lactation. The study is to analyze fatty acid content in the form of saturated fatty acids or unsaturated fat contained in breast milk. Breastmilk taken in the study was as much as 50 ml in a 250 ml erlenmeyer solution. To the sample 50 ml of concentrated, HCL concentration was added as much as 5 m and then the solution was beat for 15 minutes and was exposed ultrasonic therapy for 1 hour. The solution was then extracted using n-hexane and aquabidest solution until the milk oil solution was separated. Milk oil was extracted by adding 50 ml of Na2SO4 1 m then deciphere was performed. The breastmilk milk extraction oil was weighed 0.1 gram in a Teflon-filled reaction tube. A 15% BF3 solution in methanol was added 0.5 ml and then was heated in an air bath with a temperature of 45 ° C for 30 minutes. After cooling, solution of 0.2 ml of n-hexane was added to form two layers. The upper layer which was fatty acid methyl ester was taken by using syringe and then was injected in GC-MS. In this study, the total saturated fatty acid was 42.54% and the total unsaturated fatty acid was 57.17%. Saturated fatty acids consisted of lauric, myristic, palmitate, and stearate. Omega-6 fatty acids and monounsaturated fatty acids consisted of omega-9 fatty acids. In Mother's Milk with 9 months lactation period there are various fatty acid content of both saturated fatty acids, monounsaturated fatty acids (omega-9) and polyunsaturated fatty acids (omega-6).